Study on Machining Parameters and Mechanical Properties of Hybrid Agave Sisalana and Glass Fiber-reinforced Polyester Composites (A/GFRP). Issue 15 (23rd November 2022) - Prabhu, P.; Balaji, A.; Jayabalakrishnan, D.; Velmurugan, N.; Vimalnathan, P.; Karthikeyan, B.; Balaji, V.; Dinesh, S.
ABSTRACT: Agave fiber/polymer matrix composites have recently been used in automotive, aerospace, and construction field, where they will be secure for shape-made applications. Hand lay-up is used to make Agave and Glass fiber-reinforced polyester composites (A/GFRP), Agave fiber-reinforced polyester composites (AFRP), and Glass fiber-reinforced polyester composites (GFRP). The impact energy absorbed and tensile strength for A/GFRP material are higher than those for AFRP material. Drilling of GFRP, AFRP, and A/GFRP composites is carried out by using carbide twist drill D 5407060 of 6 mm diameter. Process parameters include two distinct speeds (800 rpm and 1200 rpm) and two distinct feeds (0.02 mm/rev and 0.04 mm/rev). The influences of processing parameters on thrust force and delamination while drilling GFRP, AFRP, and A/GFRP materials are investigated. For the optimum process parameter (feed = 0.02 mm/rev and 800 rpm) for GFRP, AFRP, and A/GFRP, the thrust force and delamination factor are limited at these feed rate conditions. In comparison to AFRP, delamination is minimum for A/GFRP drilled with carbide tools at lower feed rates as per microstructural examination. The Taguchi technique is used to determine the best feed and speed parameters for machining responses, and it demonstrates that acceptable values are achievable with A/GFRP.